2015
DOI: 10.1097/mot.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Extended release once a day tacrolimus

Abstract: Although extended release tacrolimus shows promise in improving patient adherence to transplant medication therapy, further studies are needed to confirm improved compliance and to assess long-term safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It was found that based on the result of Scr, renal function was improved after tacrolimus conversion from immediate-to extended-release formulation in renal transplant patients with a follow-up duration ≥48 weeks but not in patients with a follow-up duration <48 weeks. The possible interpretation would be that, as discussed previously, extended-release tacrolimus was in a once-daily formulation procedure, which increased medication adherence (Hatakeyama et al, 2012;Singh et al, 2015;Oh et al, 2020;Verma et al, 2023); therefore, the long-term effect of conversion to extendedrelease tacrolimus on improving the renal function in renal transplant patients was obvious. Further subgroup analysis discovered that in patients with the tacrolimus dose after conversion ≤4.0 mg/d and patients with the tacrolimus blood trough level after conversion >6.0 ng/mL, the renal function seemed to be improved.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was found that based on the result of Scr, renal function was improved after tacrolimus conversion from immediate-to extended-release formulation in renal transplant patients with a follow-up duration ≥48 weeks but not in patients with a follow-up duration <48 weeks. The possible interpretation would be that, as discussed previously, extended-release tacrolimus was in a once-daily formulation procedure, which increased medication adherence (Hatakeyama et al, 2012;Singh et al, 2015;Oh et al, 2020;Verma et al, 2023); therefore, the long-term effect of conversion to extendedrelease tacrolimus on improving the renal function in renal transplant patients was obvious. Further subgroup analysis discovered that in patients with the tacrolimus dose after conversion ≤4.0 mg/d and patients with the tacrolimus blood trough level after conversion >6.0 ng/mL, the renal function seemed to be improved.…”
Section: Discussionmentioning
confidence: 91%
“…The potential reasons would be as follows ( Goldfarb, 2021 ): an extended-release tacrolimus formulation might have a flat pharmacokinetic profile, such as higher bioavailability, less fluctuation between trough and peak exposures, and a delayed peak concentration; thus, it might have a better effect on inhibiting antibody-mediated rejection, thus improving the renal function ( Garnock-Jones, 2015 ; Oberbauer et al, 2020 ; Hart et al, 2021a ). An extended-release tacrolimus formulation only needs to be taken once daily, which might increase medication adherence, and then improved the renal function ( Singh et al, 2015 ; Oberbauer et al, 2020 ). Another finding of this meta-analysis should also be noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Here we will provide a brief overview of immunosuppressive compounds, so as to provide background for nanoparticle discussions. For more detailed information of immunosuppressive drug regimens and mechanism of action, see [reviews 29 ] and Table 1.…”
Section: Introductionmentioning
confidence: 99%